Legal Reasoning Pattern Based On Trancendental Values : A Reflection on Legal Reasoning Based on Positivism Values - Basri Basri (Law Doctoral Program Universitas Muhammadiyah Surakarta, 2019)
Purpose of the study: This article aims at finding out the pattern of legal penalties for transcendental valuesMethodology: This research is conducted using descriptive philosophical normative study methods. As a secondary legal material, this writing draws on literature, papers, journals, and research related to this writing.Main Findings: Positivism-based legal reasoning has failed to accommodate all the interests and legal needs of the community in realizing justice and prosperity. The pattern of legal reasoning based on transcendental values is a choice because it is related to the understanding that places the law for justice and public welfare.Applications of this study: This study can give benefit to thinkers in the field of legal studies thinking to make a breakthrough in the formation of new lawsNovelty/Originality of this study: The use of the basics of transcendental law can be made as a new breakthrough to realize a just and prosperous law